Preventing the Incidence of Severe Preeclampsia by Maintaining an Ideal Body Weight During Pregnancy (Majalah Kedokteran Bandung, 2025)
Preeclampsia is a pregnancy-specific disease potentially leading to complications, morbidity, and mortality. In general, obesity may cause preeclampsia through several common mechanisms. This study aimed to examine the association between obesity and the incidence of severe preeclampsia (SP) at Dr. Dradjat Prawiranegara General Hospital, Serang, Indonesia. A retrospective cohort design was used and the sample comprised of 168 parturients (84 SP and 84 non-SP subjects). Sample selection was consecutively conducted from June to November 2023, while data were analyzed using the Chi-Square test and multivariable analysis with multiple logistic regression. There was a statistically significant relationship between nutritional status and obesity in participants with SP history (p
Keywords: Body mass index; obesity; parity; severe preeclampsia; uteroplacental insufficiency